MERUMUSKAN TUJUAN LAPORAN KEUANGAN BANK SYARIAH : SEBUAH STUDI EKSPLORASI - Sofie (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2005)
This exploration study examined to construct the objective of Islamic Bank’s financial report. Begin with literature research, the objective of Islamic Bank’s financial report designed by Al-Quran and Hadits, the standar, and the previous research.First focus group with ustadzs was to confirm the result from literature research. And the second focus group with the users of Islamic Bank’s financial report and the academicians had done to maked the model better.Model of the objective of Islamic Bank’s financial report that match with Islamic syariah is the result of this research.